Chemical mechanical polishing composition and its application in chemical mechanical polishing
By using nano-scale Al2O3 abrasives and potassium ferrate coated with a small layer of graphite in SiC wafer chemical mechanical polishing technology, the problems of abrasive agglomeration and KMnO4 instability are solved, and an efficient and low-cost polishing process is achieved, improving the wafer surface quality and equipment life.
Patent Information
- Application Number
- CN202411628960.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing SiC wafer chemical mechanical polishing technology has problems such as abrasive agglomeration, KMnO4 instability and its hazards, shortened equipment life, low production efficiency and high cost.
Nanocomposite abrasives are prepared by a small layer of graphite coated nanoscale Al2O3 abrasives through a two-step calcination process, and combined with potassium ferrate as an oxidizing agent to form an alkaline chemical mechanical polishing composition.
The uniform dispersion of abrasives in the polishing liquid is achieved, the polishing efficiency and wafer surface quality are improved, the production cost is reduced, and the equipment service life is extended.
Smart Images

Figure CN119144288B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chip manufacturing, in particular to a chemical mechanical polishing composition and an application thereof in chemical mechanical polishing. Background Art
[0002] Silicon carbide (SiC) is a wide bandgap semiconductor material that occupies an important position in the modern electronics industry due to its excellent physical and chemical properties. SiC is an environmentally friendly semiconductor material. Compared with silicon, the production and manufacturing process of SiC can not only reduce dependence on earth resources, but also reduce environmental pollution and carbon emissions. SiC's high thermal conductivity, high breakdown electric field strength, high saturation electron mobility and other characteristics make it an ideal material for manufacturing high-performance power devices and radio frequency (RF) devices. These excellent properties enable SiC devices to work stably in extreme environments (such as high temperature, high pressure, and high frequency), and are widely used in many high-tech fields such as automotive electronics, aerospace, photovoltaic power generation, smart grids, and renewable energy systems. Therefore, the production of high-quality, large-size SiC wafers is of vital importance to promoting technological innovation and industrial upgrading in the above fields.
[0003] Chemical Mechanical Polishing (CMP) is a surface planarization technology that perfectly combines chemical etching with mechanical grinding. Its core lies in the synergistic effect of chemical and mechanical action. The wafer is pressed tightly against the high-speed rotating polishing pad by the polishing head. The micro-hair and tiny particles on the surface of the polishing pad are used to rub against the wafer surface to remove the oxide layer formed by chemical action, exposing the new surface. The new surface is chemically oxidized and then mechanically polished again. This cycle eventually reduces the surface roughness of the wafer to the nanometer level. CMP technology was first proposed by Monsanto in 1965 and was originally used to obtain high-quality glass surfaces. With the development of semiconductor technology, CMP technology began to be vigorously explored in the mid-1980s to meet the needs of increasing the density of integrated circuits, global planarization of smaller device structures and multi-layer metals. Since the surface of the wafer is uneven due to processes such as crystal growth and cutting, CMP technology can polish it flat, providing an ideal starting plane for subsequent processes such as lithography and etching. A flat wafer surface helps to evenly coat the photoresist and ensure the resolution and accuracy of the photolithography pattern. Therefore, as a key technology in the semiconductor manufacturing process, CMP technology is mainly used to achieve ultra-flat wafer surfaces. CMP technology combines chemical and mechanical effects. The chemical reagents in the polishing liquid react chemically with the wafer surface to soften or etch the surface material, and then these materials are effectively removed through mechanical friction on the polishing pad. This process can effectively reduce the roughness of the wafer surface and improve the surface flatness, thereby improving the performance and reliability of the device.
[0004] For the CMP process of 8-inch SiC wafers, the market currently mainly uses two different polishing liquid formulas: rough polishing liquid and fine polishing liquid. The formula of the rough polishing liquid is mainly acidic KMnO4 solution plus submicron-level α-Al2O3 abrasives. This combination can remove larger defects on the wafer surface in a shorter time, but there are problems such as unstable polishing effect, environmental pollution, equipment corrosion, and abrasive agglomeration. The fine polishing liquid uses a combination of vanadic acid and nano-silica sol, aiming to further improve the smoothness and flatness of the wafer surface to meet higher precision requirements. However, this process is complicated and involves multiple polishings, which not only reduces production efficiency and increases manufacturing costs, but may also introduce more surface defects due to multiple polishings, affecting the yield rate.
[0005] In order to ensure the quality of the wafer surface, especially to protect the silicon surface (Si-face) where epitaxial film will be grown later, the single-wafer polishing process currently used includes the following three steps: Step 1: Rough polishing of the silicon surface. First, the silicon surface of the wafer is rough polished to remove larger surface defects and prepare for subsequent steps. Step 2: Rough polishing of the carbon surface. Then the carbon surface (C-face) of the wafer is rough polished to ensure the uniformity and consistency of both sides and prevent problems caused by uneven surfaces in subsequent processing. Step 3: Fine polishing of the silicon surface. Finally, the silicon surface is finely polished again to achieve the final surface quality requirements and ensure that the surface finish and flatness meet the standards.
[0006] However, the existing technical solutions still have the following problems and shortcomings:
[0007] 1) Instability and hazards of KMnO4
[0008] Although acidic KMnO4 shows high activity in oxidation reactions, its oxidizability will significantly decrease with changes in pH, resulting in unstable polishing effects. In addition, KMnO4 will produce toxic byproducts during use, posing a potential threat to the environment and the health of operators. Therefore, this polishing liquid is not suitable for large-scale promotion and application.
[0009] 2) Impact of equipment life
[0010] The corrosiveness of KMnO4 can also damage polishing equipment and shorten its service life. This not only increases maintenance costs, but may also affect production efficiency and wafer quality. Long-term use of KMnO4 may cause premature wear of polishing pads and other key components, thus affecting the stability of the entire production process.
[0011] 3) Abrasive agglomeration problem
[0012] Submicron-level α-Al2O3 abrasives tend to aggregate in the polishing liquid to form flocculent precipitation. These aggregates will scratch the wafer surface during the polishing process, seriously affecting the wafer yield and reliability. Agglomeration not only reduces polishing efficiency, but may also cause defects on the wafer surface, thus affecting the performance of the final product.
[0013] 4) Production efficiency and cost
[0014] Although the introduction of fine polishing process can improve the quality of wafer surface, it also leads to a decrease in production efficiency. Each additional process will extend the production cycle and increase time and resource consumption. At the same time, the materials required for fine polishing will also increase the manufacturing cost, which is not conducive to large-scale production and market competition. In addition, multiple polishing may also introduce more surface defects, thereby further reducing the yield rate, which is not conducive to large-scale production and market competition.
[0015] In view of this, how to provide a mechanical polishing liquid abrasive with good dispersibility, lower cost and higher production efficiency has become a technical problem that needs to be urgently solved in this industry. Summary of the invention
[0016] In view of the above problems, the purpose of the present invention is to provide a nano-composite abrasive with good dispersibility, low cost and high production efficiency to solve the problems of abrasive agglomeration and instability of KMnO4 and its hazards in the prior art. This solution will significantly improve the polishing efficiency and surface quality of SiC wafers in the CMP process, reduce manufacturing costs, and promote the continuous progress of semiconductor manufacturing technology and industrial upgrading.
[0017] The second object of the present invention is to provide a method for preparing the nanocomposite abrasive.
[0018] The third object of the present invention is to provide a chemical mechanical polishing composition.
[0019] The fourth object of the present invention is to provide a method for preparing the chemical mechanical polishing composition.
[0020] The technical solution adopted to achieve the purpose of the present invention is:
[0021] The invention provides a nano composite abrasive, which comprises a nano-scale Al2O3 abrasive coated with a few layers of graphite, wherein the mass fraction of C element in the nano composite abrasive is not higher than 10wt.%.
[0022] In the above technical solution, the mass fraction of the C element in the nano-composite abrasive is 1wt.%-10wt.%.
[0023] In the above technical solution, the mass fraction of the C element in the nano-composite abrasive is 5wt.%-8wt.%.
[0024] In the above technical solution, the average particle size of the nano-scale Al2O3 abrasive is 50nm-100nm.
[0025] A second aspect of the present invention provides a method for preparing a nanocomposite abrasive, comprising the following steps:
[0026] Step 1, calcining the organic aluminum salt for the first time in a vacuum atmosphere to decompose the organic matter in the organic aluminum salt to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the organic aluminum salt is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0027] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere to partially decompose the nano-carbon network to obtain the nano-composite abrasive.
[0028] In the above technical solution, the temperature of the first calcination in step 1 is 700° C.-1000° C., and the time of the first calcination is 20 min-40 min.
[0029] In the above technical solution, the temperature of the second calcination in step 2 is 450°C-600°C, and the time of the second calcination is 30min-40min.
[0030] In the above technical solution, the organic aluminum salt is one or more of aluminum lactate, aluminum stearate, aluminum citrate or aluminum acetate.
[0031] The third aspect of the present invention provides a chemical mechanical polishing composition, comprising an oxidant, the nanocomposite abrasive or the nanocomposite abrasive prepared by the preparation method, a suspending agent, a pH regulator and a balance of solvent.
[0032] In the above technical solution, the chemical mechanical polishing composition includes 5wt.%-7wt.% of nano-composite abrasive, 1wt.%-3wt.% of oxidant, 0.5wt.%-2.5wt.% of pH adjuster, 0.5wt.%-2wt.% of suspending agent and the balance of solvent.
[0033] In the above technical solution, the oxidant is potassium ferrate.
[0034] In the above technical solution, the pH value of the chemical mechanical polishing composition is not less than 10.
[0035] In the above technical solution, the pH value of the chemical mechanical polishing composition is 10-12.
[0036] In the above technical solution, the pH regulator is any one of ethylenediamine, ethanolamine or betaine.
[0037] In the above technical solution, the suspending agent is any one of hydrated magnesium silicate, polyacrylic acid solution or urea-modified polyurethane solution.
[0038] In the above technical solution, the removal rate of the chemical mechanical polishing composition for polishing the silicon surface is greater than 4µm / h, and the removal rate of the chemical mechanical polishing composition for polishing the carbon surface is greater than 10µm / h.
[0039] In a fourth aspect of the present invention, a method for preparing a chemical mechanical polishing composition is provided, wherein the nano-composite abrasive or the nano-composite abrasive prepared by the preparation method is uniformly mixed with the oxidant described in the above technical scheme and the suspending agent described in the above technical scheme in a solvent, and then the pH adjuster described in the above technical scheme is added to adjust the pH value, and then the chemical mechanical polishing composition is obtained after dispersion.
[0040] In the above technical solution, the pH value of the chemical mechanical polishing composition is 10-12.
[0041] In the above technical solution, the dispersion process is ball milling dispersion for 1h-3h and ultrasonication for 15min-45min.
[0042] A fifth aspect of the present invention provides an application of the chemical mechanical polishing composition or the chemical mechanical polishing composition prepared by the preparation method in SiC polishing.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] a. The present invention prepares a nano-scale Al2O3 abrasive coated with a few layers of graphite through a two-step calcination process. The present invention successfully replaces the covalent chemical bonds between traditional Al2O3 particles by introducing the van der Waals force between graphite layers at the abrasive interface. The breakthrough is that even without adding a dispersant and a silane coupling agent, the nano-composite abrasive provided by the present invention can achieve uniform dispersion of the abrasive in the polishing liquid. This feature not only reduces the production cost of the polishing liquid, but also the uniform dispersion advantage of the abrasive in the present invention will not decrease with the change of the pH value of the polishing liquid, ensuring the consistency and efficiency of the polishing process. In addition, the uniformly dispersed abrasive particles can contact the wafer surface more effectively during the polishing process, so that while ensuring the rough polishing efficiency, the wafer surface after rough polishing has excellent roughness and effectively reduces the risk of surface scratches, laying a solid foundation for subsequent precision processing and device performance improvement.
[0045] b. The present invention successfully prepares an alkaline polishing liquid of potassium ferrate (K2FeO4) + nano-sized Al2O3 with uniformly dispersed abrasives. K2FeO4 has a higher redox potential than KMnO4 in an alkaline environment and is more environmentally friendly. The high stability of K2FeO4 under alkaline conditions can make up for the problem of insufficient chemical action of KMnO4 in an alkaline environment, providing a more stable and environmentally friendly oxidant option for the CMP process; at the same time, due to the uniform dispersion of the abrasive, the abrasive particles in the polishing liquid can more fully contact the wafer surface, significantly enhancing the mechanical friction effect, thereby improving the polishing efficiency and the flatness of the wafer surface. The dual improvements in chemical and mechanical effects of the present invention make the SiC alkaline polishing liquid technically have the potential to completely replace the current commercial acid polishing liquid.
[0046] c. Under the same polishing pressure conditions, an 8-inch SiC substrate was polished using the uniformly dispersed nano-abrasive alkaline chemical mechanical polishing composition provided by the present invention. The process technical indicators such as the surface roughness Ra and the total scratch length of the SiC substrate showed excellent performance that was superior to the currently commercially available acidic KMnO4 system polishing liquid. This achievement not only proves the significant advantages of the polishing liquid of the present invention in improving the surface quality of wafers, but also provides reliable technical guarantees for subsequent high-precision processing links such as thin film epitaxial growth, laying a solid foundation for performance improvement and reliability enhancement of semiconductor devices.
[0047] In summary, the present invention has achieved multiple breakthroughs in CMP technology through innovative preparation processes and unique polishing liquid formulas, which not only improves polishing efficiency and wafer surface quality, but also reduces production costs, thereby promoting the continuous advancement of semiconductor manufacturing technology and industrial upgrading. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0049] Figure 1 The figure shows the polishing rate of the silicon surface and the carbon surface after polishing 20 SiC substrates using a commercial acidic potassium permanganate system polishing liquid;
[0050] Figure 2 The figure shows the surface roughness of the silicon surface of the SiC substrate after polishing using a commercial acidic potassium permanganate system polishing solution;
[0051] Figure 3The figure shows the surface roughness of the carbon surface of the SiC substrate after polishing using a commercial acidic potassium permanganate system polishing solution;
[0052] Figure 4 The figure shows the surface defect detection of SiC substrate after rough polishing using commercial acidic potassium permanganate system polishing liquid;
[0053] Figure 5 Shown is a particle size analysis diagram of the nano-alumina composite abrasive coated with a few layers of graphite in Example 1 of the present invention;
[0054] Figure 6 The EDS spectrum of the composite abrasive after the first calcination in Example 1 of the present invention is shown;
[0055] Figure 7 The EDS spectrum of the composite abrasive after the second calcination in Example 1 of the present invention is shown;
[0056] Figure 8 The figure shows the polishing rate of the silicon surface and the carbon surface after polishing 20 SiC substrates using the alkaline chemical mechanical polishing composition prepared in Example 9 of the present invention;
[0057] Fig. 9 The figure shows the surface roughness of the silicon surface of the SiC substrate after polishing using the alkaline chemical mechanical polishing composition prepared in Example 9 of the present invention;
[0058] Fig.10 The figure shows the surface roughness of the carbon surface of the SiC substrate after polishing using the alkaline chemical mechanical polishing composition prepared in Example 9 of the present invention;
[0059] Fig.11 Shown is a surface defect detection diagram of a SiC substrate after rough polishing using the alkaline chemical mechanical polishing composition prepared in Example 9 of the present invention. DETAILED DESCRIPTION
[0060] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0061] In the present invention, chemical mechanical polishing (CMP) is also called chemical mechanical planarization (CMP), and wafer (Wafer, W) is also called substrate or base plate (Substrate), and their meanings and actual functions are equivalent.
[0062] The present invention provides a nano-composite abrasive, comprising a graphite-coated nano-scale Al2O3 abrasive, wherein the mass fraction of the C element in the nano-composite abrasive is not higher than 10wt.%. In the nano-composite abrasive provided by the present invention, the content of the C element is preferably 1wt.%-10wt.%, and more preferably 5wt.%-8wt.%. The present invention controls the content of the C element in the nano-composite abrasive to within 10wt.%, thereby avoiding the insufficient mechanical removal effect caused by excessively high C content, and ensuring the polishing efficiency of substrates and wafers.
[0063] In the present invention, the average particle size of the nano-scale Al2O3 abrasive is preferably 50nm-100nm, more preferably 60-80nm.
[0064] The nano-scale Al2O3 abrasive coated with a few layers of graphite provided by the present invention replaces the covalent chemical bonds between Al2O3 particles by introducing the inter-graphite Van der Waals force at the abrasive interface, and can achieve uniform dispersion of the abrasive in the polishing liquid without adding a dispersant and a silane coupling agent, thereby reducing the production cost of the polishing liquid, and the uniform dispersion advantage of the abrasive in the present invention will not decrease with the change of the pH value of the polishing liquid. At the same time, the uniformly dispersed abrasive can make the wafer surface after rough polishing have excellent roughness and effectively reduce surface scratches.
[0065] The second aspect of the present invention provides a method for preparing the nanocomposite abrasive according to the above technical solution, comprising the following steps:
[0066] Step 1, calcining the organic aluminum salt for the first time in a vacuum atmosphere to decompose the organic matter in the organic aluminum salt to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the organic aluminum salt is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0067] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere to partially decompose the nano-carbon network to obtain the nano-composite abrasive.
[0068] In the present invention, the temperature for the first calcination of the organic aluminum salt in step 1 is preferably 700°C-1000°C, more preferably 800°C; the time for the first calcination is preferably 20min-40min, more preferably 30min. In the present invention, preferably after the first calcination, the content of C element in the initial form of the composite abrasive is 20wt.%-30wt.%. The purpose of the first calcination of the organic aluminum salt in the present invention is to exert the spatial confinement effect of the nanocarbon network so as to obtain an aluminum oxide abrasive with a nanometer particle size.
[0069] The temperature of the second calcination in step 2 is preferably 450°C-600°C, more preferably 500°C; the time of the second calcination is preferably 30min-40min, more preferably 30min. The second calcination of the present invention is carried out in the air. Due to the presence of oxygen in the air, the raw materials burn more fully during the calcination process, and more C elements will participate in the reaction, and finally the C element content in the composite abrasive is controlled within 10% to prevent the C content from being too high and reduce the polishing removal rate.
[0070] In the present invention, the organic aluminum salt is preferably one or more of aluminum lactate, aluminum stearate, aluminum citrate or aluminum acetate. The aluminum salt of the present invention is selected from aluminum lactate, aluminum stearate, aluminum citrate or aluminum acetate, which can convert the organic C element into a carbon nano network during high-temperature calcination, and finally into nano-alumina coated with a graphite layer.
[0071] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0072] Step 1, in a vacuum atmosphere, calcining aluminum lactate for the first time at a temperature of 800° C. for 30 min, so that organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0073] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 20 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0074] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0075] Step 1, in a vacuum atmosphere, calcining aluminum stearate for the first time at a temperature of 800° C. for 30 min, so that organic matter in the aluminum stearate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum stearate is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0076] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0077] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0078] Step 1, calcining aluminum citrate for the first time in a vacuum atmosphere at a temperature of 800° C. for 30 min, so that organic matter in the aluminum citrate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum citrate is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0079] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0080] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0081] Step 1, calcining aluminum acetate for the first time in a vacuum atmosphere at a temperature of 800° C. for 30 minutes, so that the organic matter in the aluminum acetate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum acetate is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0082] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0083] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0084] Step 1, in a vacuum atmosphere, calcining aluminum lactate for the first time at a temperature of 700° C. for 40 minutes, so that organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0085] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0086] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0087] Step 1, in a vacuum atmosphere, calcining aluminum lactate for the first time at a temperature of 800° C. for 30 min, so that organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0088] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 450° C. for 40 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0089] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0090] Step 1, in a vacuum atmosphere, calcining aluminum lactate for the first time at a temperature of 800° C. for 30 min, so that organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0091] Step 2, calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 600° C. for 30 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite;
[0092] In a preferred embodiment of the present invention, the preparation method consists of the following steps:
[0093] Step 1, in a vacuum atmosphere, calcining aluminum lactate for the first time at a temperature of 1000° C. for 20 min, so that organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and aluminum oxide obtained by decomposing the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0094] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0095] On this basis, the present invention also provides a chemical mechanical polishing composition, comprising an oxidant, the nanocomposite abrasive described in the above technical solution or the nanocomposite abrasive prepared by the preparation method described in the above technical solution, a suspending agent, a pH regulator and a balance of solvent. It should be noted that in the present invention, the chemical mechanical polishing composition is a chemical mechanical polishing slurry.
[0096] In the present invention, the chemical mechanical polishing composition preferably includes 5wt.%-7wt.% of nanocomposite abrasive, 1wt.%-3wt.% of oxidizing agent, 0.5wt.%-2.5wt.% of pH adjusting agent, 0.5wt.%-2wt.% of suspending agent and the balance of solvent.
[0097] In a preferred embodiment of the present invention, the chemical mechanical polishing composition comprises 6wt.% of nano-composite abrasive, 2wt.% of oxidant, 1wt.% of suspending agent and the balance solvent; in a preferred embodiment of the present invention, the chemical mechanical polishing composition comprises 7wt.% of nano-composite abrasive, 2wt.% of oxidant, 1.5wt.% of suspending agent and the balance solvent.
[0098] In the present invention, the content of the nano-composite abrasive in the chemical mechanical polishing composition is preferably 5wt.%-7wt.%, more preferably 5wt.% or 5.5wt.% or 6wt.% or 6.5wt.% or 7wt.%, and more preferably 6wt.%. The present invention controls the content of the nano-composite abrasive in the chemical mechanical polishing composition to ensure sufficient mechanical removal capacity while ensuring uniformity and surface quality of the polishing process. In addition, the amount of abrasive directly affects the material removal rate. An appropriate amount of abrasive can ensure a higher removal rate while avoiding surface damage caused by excessive abrasive.
[0099] In the present invention, the oxidant in the chemical mechanical polishing composition is preferably potassium ferrate, and the content of the oxidant is preferably 1wt.%-3wt.%, further preferably 1wt.% or 1.2wt.% or 1.5wt.% or 1.8wt.% or 2.0wt.% or 2.2wt.% or 2.5wt.% or 2.8wt.% or 3.0wt.%, and more preferably 2wt.%; the present invention selects potassium ferrate as the oxidant. On the one hand, K2FeO4 has a higher redox potential than KMnO4 in an alkaline environment, and is more environmentally friendly; on the other hand, K2FeO4 is very stable under alkaline conditions, which can make up for the lack of chemical action of KMnO4 in an alkaline environment; in addition, potassium ferrate is very stable at room temperature, which helps to maintain the performance of the polishing liquid and extend its service life. The reduction product of potassium ferrate also has flocculation and adsorption effects, is harmless to the body, and is more environmentally friendly.
[0100] In the present invention, the pH regulator in the chemical mechanical polishing composition is preferably any one of ethylenediamine, ethanolamine or betaine, and the content of the pH regulator is preferably 0.5wt.%-2.5wt.%; the pH regulator of the present invention is selected from ethylenediamine, ethanolamine or betaine, which can slowly release their own hydroxyl groups to balance the pH value of the polishing liquid, play a pH buffering role, maintain the stability of the chemical environment in the polishing liquid, optimize the surface roughness of the substrate, and form a passivation film on the substrate surface to increase the material removal rate; when ethylenediamine (EDA) is used for polishing silicon materials, it can also polarize silicon atoms to form oxides, and use the mechanical friction of abrasive particles to achieve rapid polishing and improve polishing efficiency. If a strong base is used as a pH regulator, other metal ions may be introduced to contaminate the surface of the material. The pH regulator selected by the present invention effectively avoids this risk and further ensures the purity of the polishing material. In addition, compared with inorganic acids and inorganic bases, the polishing liquid adjusted by organic bases can provide a more stable polishing environment during long-term storage and use.
[0101] In the present invention, the suspending agent in the chemical mechanical polishing composition is preferably any one of hydrated magnesium silicate, polyacrylic acid solution or urea modified polyurethane solution, more preferably hydrated magnesium silicate; the content of the suspending agent is preferably 0.5wt.%-2wt.%, further preferably 0.5wt.% or 0.55wt.% or 0.6wt.% or 0.8wt.% or 1wt.% or 1.2wt.% or 1.5.% or 1.8wt.% or 2wt.%, more preferably 1.5wt.%. The present invention uses hydrated magnesium silicate or urea modified polyurethane solution as a suspending agent, which can stably function under alkaline conditions and will not chemically react with nano alumina, which helps to improve the dispersibility and stability of the abrasive in the chemical mechanical polishing composition, thereby improving the polishing efficiency and surface quality.
[0102] In the present invention, the pH of the chemical mechanical polishing composition is preferably not less than 10, more preferably 10-12, more preferably 10-11, and more preferably 10.5. The present invention controls the pH value of the chemical mechanical polishing composition to 10-12, which can ensure that K2FeO4 has a high redox potential, ensure its polishing effect, and ensure the quality of the polished surface. At the same time, the pH value is controlled to be no higher than 12, which can reduce the use of strong alkali, reduce pollution to the environment, and also ensure the safety of operators. In addition, the chemical mechanical polishing composition provided by the present invention does not have a significant disadvantage in terms of removal rate compared with commercial acidic polishing liquids.
[0103] The removal rate of the chemical mechanical polishing composition provided by the present invention for polishing silicon surfaces is preferably greater than 4µm / h, and the removal rate of the chemical mechanical polishing composition for polishing carbon surfaces is preferably greater than 10µm / h. The chemical mechanical polishing composition provided by the present invention exhibits different removal rates when polishing silicon surfaces and carbon surfaces, which not only significantly improves processing efficiency and surface quality, shortens production cycles, but also increases process flexibility and material selectivity, is environmentally friendly, and helps to improve the quality and reliability of the final product.
[0104] The nano-abrasive alkaline chemical mechanical polishing composition provided by the present invention is evenly dispersed. After polishing an 8-inch SiC substrate, its process technical indicators such as surface roughness Ra and total scratch length are better than those of the currently commercially available acidic KMnO4 system polishing liquid. The high-quality crystal surface quality of the nano-abrasive provides technical guarantee for subsequent thin film epitaxial growth.
[0105] The present invention also provides a method for preparing the chemical mechanical polishing composition described in the above technical solution, comprising the following steps: uniformly mixing the nano-composite abrasive described in the above technical solution or the nano-composite abrasive prepared by the preparation method with the oxidant described in the above technical solution and the suspending agent described in the above technical solution in a solvent, adding the pH adjuster described in the above technical solution to adjust the pH value, and then dispersing to obtain the chemical mechanical polishing composition.
[0106] In the present invention, the solvent is preferably deionized water (DIW).
[0107] In the present invention, the pH value is preferably adjusted as follows: the pH value is adjusted so that the pH value of the chemical mechanical polishing composition is 10-12; the dispersion process is preferably ball milling dispersion for 1h-3h, and ultrasonication for 15min-45min. The time for ball milling dispersion in the present invention is preferably 1h-3h, more preferably 2h; the time for ultrasonication is preferably 15min-45min, more preferably 30min. The ball milling dispersion and ultrasonication in the present invention help to evenly disperse the abrasive, thereby increasing the effective contact area between the abrasive and the wafer, and improving the mechanical action between the abrasive and the wafer surface. The preparation method provided by the present invention simultaneously improves the chemical composition of the abrasive, improves the mechanical action between the abrasive and the wafer surface, and makes it possible for SiC alkaline polishing liquid to replace the current commercial acidic polishing liquid.
[0108] In a preferred embodiment of the present invention, the preparation method of the chemical mechanical polishing composition comprises the following steps: after uniformly mixing the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method, the oxidant described in the above technical scheme, and the suspending agent described in the above technical scheme in a solvent, adding the pH adjuster described in the above technical scheme to adjust the pH value to 10.2, and then dispersing to obtain the chemical mechanical polishing composition; in terms of mass percentage, the amount of the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method is 6wt.%, the oxidant is potassium ferrate, the amount of the oxidant is 2wt.%, the suspending agent is hydrated magnesium silicate, the amount of the suspending agent is 1wt.%, the pH adjuster is ethylenediamine, and the solvent is deionized water; the dispersion is ball milling dispersion for 2h, and ultrasonication is performed for 30min.
[0109] In a preferred embodiment of the present invention, the preparation method of the chemical mechanical polishing composition comprises the following steps: after uniformly mixing the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method, the oxidant described in the above technical scheme and the suspending agent described in the above technical scheme in a solvent, adding the pH adjuster described in the above technical scheme to adjust the pH value to 10.2, and then dispersing to obtain the chemical mechanical polishing composition; the amount of the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method is 7wt.%, the oxidant is potassium ferrate, the amount of the oxidant is 2wt.%, the suspending agent is hydrated magnesium silicate, the amount of the suspending agent is 1.5wt.%, the pH adjuster is ethylenediamine, and the solvent is deionized water; the dispersion is ball milling dispersion for 2h, and ultrasonication is performed for 30min.
[0110] In a preferred embodiment of the present invention, the preparation method of the chemical mechanical polishing composition comprises the following steps: after uniformly mixing the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method, the oxidant described in the above technical scheme and the suspending agent described in the above technical scheme in a solvent, adding the pH adjuster described in the above technical scheme to adjust the pH value to 10.2, and then dispersing to obtain the chemical mechanical polishing composition; in terms of mass percentage, the amount of the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method is 6wt.%, the oxidant is potassium ferrate, the amount of the oxidant is 2wt.%, the suspending agent is hydrated magnesium silicate, the amount of the suspending agent is 1wt.%, the pH adjuster is ethylenediamine, and the solvent is deionized water; the dispersion is ball milling dispersion for 3h, and ultrasonication is performed for 30min.
[0111] In a preferred embodiment of the present invention, the preparation method of the chemical mechanical polishing composition comprises the following steps: after uniformly mixing the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method, the oxidant described in the above technical scheme, and the suspending agent described in the above technical scheme in a solvent, adding the pH adjuster described in the above technical scheme to adjust the pH value to 10.2, and then dispersing to obtain the chemical mechanical polishing composition; in terms of mass percentage, the amount of the nano-composite abrasive described in the above technical scheme or the nano-composite abrasive prepared by the preparation method is 6wt.%, the oxidant is potassium ferrate, the amount of the oxidant is 2wt.%, the suspending agent is hydrated magnesium silicate, the amount of the suspending agent is 1wt.%, the pH adjuster is ethylenediamine, and the solvent is deionized water; the dispersion is ball milling dispersion for 2h, and ultrasonication is performed for 45min.
[0112] Based on the advantages of the chemical mechanical polishing composition described in the above technical solution or the chemical mechanical polishing composition prepared by the preparation method described in the above technical solution, the application of the chemical mechanical polishing composition described in the above technical solution or the chemical mechanical polishing composition prepared by the preparation method described in the above technical solution in SiC polishing also falls within the protection scope of the present invention.
[0113] In order to further illustrate the present invention, the nanocomposite abrasive and chemical mechanical polishing composition provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the protection scope of the present invention.
[0114] Comparative Example 1: The formula of the commercial acidic potassium permanganate polishing liquid mainly comprises 3 wt.% of KMnO4 and submicron Al2O3 abrasive with a solid content of 12 wt.%.
[0115] At 7 psi pressure, 20 pieces of 8-inch SiC substrate were polished continuously using the above commercial acidic potassium permanganate polishing solution. The results are as follows: Figure 1-Figure 4 As shown; among them, Figure 1 This is the polishing rate diagram of the silicon surface and carbon surface after polishing an 8-inch SiC substrate using a commercial acidic potassium permanganate system polishing liquid. Figure 2 The surface roughness of the silicon surface of the SiC substrate after polishing with a commercial acidic potassium permanganate system polishing solution is shown in Figure 2. Figure 3 The surface roughness of the carbon surface of the SiC substrate after polishing with a commercial acidic potassium permanganate system polishing solution is shown in Figure 2. Figure 4 This is a surface defect detection image of a SiC substrate after rough polishing with a commercial acidic potassium permanganate system polishing solution.
[0116] Depend on Figure 1It can be seen that after polishing an 8-inch SiC substrate using a commercial acidic potassium permanganate polishing solution, the average removal rate of the silicon surface is 4.92µm / h, and the average removal rate of the carbon surface is 13.94µm / h. Figure 2 It can be seen that after polishing an 8-inch SiC substrate using a commercial acidic potassium permanganate polishing solution, the silicon surface roughness is 0.097nm. Figure 3 It can be seen that after polishing an 8-inch SiC substrate using a commercial acidic potassium permanganate polishing solution, the carbon surface roughness is 0.363 nm.
[0117] Depend on Figure 4 It can be seen that the surface defects of the SiC substrate after rough polishing with commercial acidic potassium permanganate polishing liquid are as follows: the total length of the scratches is 5.04 mm. This is because the aluminum oxide abrasive is easy to agglomerate in the polishing liquid, so scratches are always inevitable on the wafer surface.
[0118] Embodiment 1, a nano composite abrasive, is prepared by the following method:
[0119] Step 1: After fine grinding of 2500g of aluminum lactate, the aluminum lactate is calcined for the first time in a vacuum atmosphere at a temperature of 800°C for 30 minutes, so that the organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive. Its EDS spectrum is as follows: Figure 6 As shown in Table 1 Figure 6 The corresponding spectrum data.
[0120] Table 1 Figure 6 The corresponding spectrum data
[0121] element Mass fraction [%] Atomic Percentage[%] O 40.37 44.55 Al 39.49 25.84 C 20.14 29.61 100.00 100.00
[0122] Step 2, in an air atmosphere, the initial composite abrasive is calcined for a second time at a temperature of 500°C for 20 min to partially decompose the nano-carbon network to obtain a nano-alumina composite abrasive coated with a few layers of graphite, the EDS spectrum of which is shown in FIG. Figure 7 As shown in Table 2 Figure 7 The corresponding spectrum data.
[0123] Table 2 Figure 7 The corresponding spectrum data
[0124] element Mass fraction [%] Atomic Percentage[%] O 51.00 37.55 Al 43.79 54.08 C 5.21 8.57 100.00 100.00
[0125] The particle size analysis of nano-alumina composite abrasive is shown in the figure Figure 5 As shown, Figure 5 (a) is a scanning electron microscope image. Figure 5 (b) is the particle size distribution diagram; Figure 5It can be seen that the average particle size of the nano-alumina prepared by the method provided by the present invention is 75.74 nm.
[0126] Embodiment 2, a nano composite abrasive, is prepared by the following method:
[0127] Step 1, taking 2000g of aluminum stearate and finely grinding it, and then calcining the aluminum stearate for the first time in a vacuum atmosphere at a calcination temperature of 800°C and a calcination time of 30min, so that the organic matter in the aluminum stearate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum stearate is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0128] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0129] Embodiment 3, a nano composite abrasive, is prepared by the following method:
[0130] Step 1, taking 2000g of aluminum citrate and grinding it finely, and then calcining the aluminum citrate for the first time in a vacuum atmosphere at a temperature of 800°C and a calcination time of 30min, so that the organic matter in the aluminum citrate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum citrate is dispersed in the nano-carbon network to obtain a composite abrasive in an initial form;
[0131] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0132] Embodiment 4, a nano composite abrasive, is prepared by the following method:
[0133] Step 1, after finely grinding 2000g of aluminum acetate, calcining the aluminum acetate for the first time in a vacuum atmosphere at a temperature of 800°C for 30 minutes, so that the organic matter in the aluminum acetate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum acetate is dispersed in the nano-carbon network to obtain a composite abrasive in the initial form;
[0134] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0135] Embodiment 5, a nano composite abrasive, is prepared by the following method:
[0136] Step 1, after finely grinding 2500g of aluminum lactate, calcining the aluminum lactate for the first time in a vacuum atmosphere at a temperature of 700°C for 40 minutes, so that the organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0137] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0138] Embodiment 6, a nano composite abrasive, is prepared by the following method:
[0139] Step 1, after finely grinding 2500g of aluminum lactate, calcining the aluminum lactate for the first time in a vacuum atmosphere at a temperature of 1000°C for 20 minutes, so that the organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0140] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 500° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0141] Embodiment 7, a nano composite abrasive, is prepared by the following method:
[0142] Step 1, after finely grinding 2500g of aluminum lactate, calcining the aluminum lactate for the first time in a vacuum atmosphere at a temperature of 800°C for 30 minutes, so that the organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0143] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 450° C. for 40 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0144] Embodiment 8, a nano composite abrasive, is prepared by the following method:
[0145] Step 1, after finely grinding 2500g of aluminum lactate, calcining the aluminum lactate for the first time in a vacuum atmosphere at a temperature of 800°C for 30 minutes, so that the organic matter in the aluminum lactate is decomposed to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the aluminum lactate is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive;
[0146] Step 2: calcining the initial composite abrasive for a second time in an air atmosphere at a temperature of 600° C. for 30 minutes to partially decompose the nano-carbon network and obtain a nano-alumina composite abrasive coated with a few layers of graphite.
[0147] Example 9, a chemical mechanical polishing composition, prepared by the following method:
[0148] According to the mass percentage, 6wt.% of nano-composite abrasive, 2wt.% of oxidant, 1wt.% of suspending agent and the rest of solvent were mixed respectively, the pH value was adjusted to 10.2 with ethylenediamine, and the mixture was dispersed by ball milling for 2h using a planetary ball mill, and then ultrasonicated for 30min to obtain a chemical mechanical polishing composition suitable for polishing SiC.
[0149] The nano-composite abrasive is the nano-composite abrasive prepared in Example 1, the oxidant is potassium ferrate, the suspending agent is hydrated magnesium silicate, and the solvent is deionized water.
[0150] At a pressure of 7 psi, 20 8-inch SiC substrates were polished continuously using the polishing liquid made of the above materials. The results are as follows: Figure 8-Figure 11 As shown, Figure 8 The polishing rate diagram of the silicon surface and carbon surface of the SiC substrate after polishing. Fig. 9 is the surface roughness of the silicon surface of the SiC substrate after polishing, Fig.10 is the surface roughness of the carbon surface of the SiC substrate after polishing, Fig.11 This is the surface defect detection image of the SiC substrate after polishing.
[0151] Depend on Figure 8 It can be seen that after polishing an 8-inch SiC substrate using the alkaline chemical mechanical polishing composition provided by the present invention, the average removal rate of the silicon surface of the SiC substrate can reach 4.2 μm / h, and the average removal rate of the carbon surface can reach 10.5 μm / h. Figure 9-10 It can be seen that the carbon surface roughness of the SiC substrate can be reduced to 0.221nm. Fig.11 It can be seen that the present invention has the surface defects of the SiC substrate after rough polishing with an abrasive alkaline polishing liquid: no surface scratches are generated.
[0152] Example 10, a chemical mechanical polishing composition, prepared by the following method:
[0153] According to the mass percentage, 7wt.% of nano-composite abrasive, 2wt.% of oxidant, 1.5wt.% of suspending agent and the rest of solvent were mixed, the pH value was adjusted to 10.6 with ethylenediamine, and the SiC chemical mechanical polishing composition was obtained after ball milling dispersion for 2h using a planetary ball mill and ultrasonication for 30min.
[0154] The nano-composite abrasive is the nano-composite abrasive prepared in Example 2, the oxidant is potassium ferrate, the suspending agent is hydrated magnesium silicate, and the solvent is deionized water.
[0155] Under a pressure of 7psi, the polishing liquid made of the above material was used to continuously polish 20 8-inch SiC substrates. As a result, the average removal rate of the silicon surface could stably reach 4.5µm / h, and the average removal rate of the carbon surface could reach 10.8µm / h. Moreover, the rate stability was high without obvious reduction, and surface scratches were avoided.
[0156] Example 11, a chemical mechanical polishing composition, prepared by the following method:
[0157] According to the mass percentage, 6wt.% of nano-composite abrasive, 2wt.% of oxidant, 1wt.% of suspending agent and the rest of solvent were mixed respectively, the pH value was adjusted to 10.2 with ethylenediamine, and the mixture was dispersed by ball milling for 3h using a planetary ball mill, and then ultrasonicated for 30min to obtain a chemical mechanical polishing composition suitable for polishing SiC.
[0158] The nano-composite abrasive is the nano-composite abrasive prepared in Example 1, the oxidant is potassium ferrate, the suspending agent is hydrated magnesium silicate, and the solvent is deionized water.
[0159] Example 12, a chemical mechanical polishing composition, prepared by the following method:
[0160] According to the mass percentage, 6wt.% of nano-composite abrasive, 2wt.% of oxidant, 1wt.% of suspending agent and the rest of solvent were mixed respectively, the pH value was adjusted to 10.2 with ethylenediamine, and the mixture was dispersed by ball milling for 2h using a planetary ball mill, and then ultrasonicated for 45min to obtain a chemical mechanical polishing composition suitable for polishing SiC.
[0161] The nano-composite abrasive is the nano-composite abrasive prepared in Example 1, the oxidant is potassium ferrate, the suspending agent is hydrated magnesium silicate, and the solvent is deionized water.
[0162] It can be seen from the above embodiments that the nanocomposite abrasive prepared by the method provided by the present invention is uniformly dispersed. Under the same polishing pressure conditions, after one-step polishing of an 8-inch SiC substrate using the alkaline chemical mechanical polishing composition prepared by the nanocomposite abrasive provided by the present invention, its process technical indicators such as roughness Ra and surface scratch defects are better than those of the currently commercially available acidic KMnO4 system polishing liquid, and the high-quality crystal surface quality provides technical guarantee for the subsequent thin film epitaxial growth.
[0163] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A nanocomposite abrasive for chemical mechanical polishing, characterized in that: The nano-composite abrasive comprises a nano-scale Al2O3 abrasive coated with a few-layer graphite, wherein the mass fraction of the C element in the nano-composite abrasive is 5wt.%-8wt.%, and the covalent chemical bonds between Al2O3 particles are replaced by the van der Waals force between graphite layers at the abrasive interface, so that the abrasive is evenly dispersed in the polishing liquid without adding a dispersant and a silane coupling agent; the few-layer graphite is obtained by two-step calcination of an organic aluminum salt, wherein the first calcination is in a vacuum atmosphere, so that the organic matter in the organic aluminum salt is decomposed to form a nano-carbon network, the calcination temperature is 700°C-1000°C, and the calcination time is 20min-40min; the second calcination is in an air atmosphere, the calcination temperature is 450°C-600°C, and the calcination time is 30min-40min, so that the nano-carbon network is partially decomposed to form a nano-scale Al2O3 abrasive coated with a few-layer graphite; the organic aluminum salt is one or more of aluminum lactate, aluminum stearate, aluminum citrate or aluminum acetate.
2. The nanocomposite abrasive according to claim 1, characterized in that: The average particle size of the nano-scale Al2O3 abrasive is 50-100nm.
3. The method for preparing the nanocomposite abrasive according to claim 1, characterized in that: The following steps are involved: Step 1, in a vacuum atmosphere, calcining the organic aluminum salt for the first time to decompose the organic matter in the organic aluminum salt to form a nano-carbon network, and the aluminum oxide obtained by the decomposition of the organic aluminum salt is dispersed in the nano-carbon network to obtain the initial form of the composite abrasive; Step 2, in an air atmosphere, calcining the initial form of the composite abrasive for the second time to partially decompose the nano-carbon network to obtain the nano-composite abrasive.
4. A chemical mechanical polishing composition, characterized in that The chemical mechanical polishing composition comprises an oxidizing agent, the nanocomposite abrasive according to claim 1 or the nanocomposite abrasive prepared by the preparation method according to claim 3, a suspending agent, a pH adjusting agent and a balance of a solvent.
5. The chemical mechanical polishing composition according to claim 4, characterized in that: The chemical mechanical polishing composition comprises 5wt.%-7wt.% of nano-composite abrasive, 1wt.%-3wt.% of oxidizing agent, 0.5wt.%-2.5wt.% of pH adjusting agent, 0.5wt.%-2wt.% of suspending agent and the balance of solvent.
6. The chemical mechanical polishing composition according to claim 4, characterized in that: The oxidant is potassium ferrate.
7. The chemical mechanical polishing composition according to claim 4, characterized in that The pH of the chemical mechanical polishing composition is not less than 10.
8. The chemical mechanical polishing composition according to claim 4, characterized in that The pH value of the chemical mechanical polishing composition is 10-12.
9. The chemical mechanical polishing composition according to claim 4, characterized in that: The pH regulator is any one of ethylenediamine, ethanolamine or betaine.
10. The chemical mechanical polishing composition according to claim 4, characterized in that: The suspending agent is any one of hydrated magnesium silicate, polyacrylic acid solution or urea-modified polyurethane solution.
11. The chemical mechanical polishing composition according to claim 4, characterized in that: The chemical mechanical polishing composition has a removal rate of more than 4 μm / h for polishing a silicon surface, and a removal rate of more than 10 μm / h for polishing a carbon surface.
12. The method for preparing the chemical mechanical polishing composition according to claim 4, characterized in that: The method comprises the following steps: uniformly mixing the nanocomposite abrasive according to claim 1 or the nanocomposite abrasive prepared by the preparation method according to claim 3, the oxidant according to claim 5 and the suspending agent according to claim 5 in a solvent, adding the pH adjuster according to claim 5 to adjust the pH value, and then dispersing the mixture to obtain the chemical mechanical polishing composition.
13. The method for preparing the chemical mechanical polishing composition according to claim 12, characterized in that: The pH value of the chemical mechanical polishing composition is 10-12.
14. The method for preparing the chemical mechanical polishing composition according to claim 12, wherein: The dispersion process is ball milling dispersion for 1h-3h and ultrasonication for 15min-45min.
15. Use of the chemical mechanical polishing composition according to claim 4 in SiC polishing.
Citation Information
Patent Citations
Silicon carbide polishing solution and preparation method thereof
CN117603624A
Alpha alumina-based abrasive grain containing silica and iron oxide
CN1188465A
Precision polishing composition
JP1991277683A